2020
DOI: 10.1080/16258312.2020.1816361
|View full text |Cite
|
Sign up to set email alerts
|

Digital supply chain: challenges and future directions

Abstract: The editorial discusses the current developments, challenges and research opportunities in digital supply chain management. First, the emerging theorization on digital supply chain is introduced and focuses on innovative technologies (big data, cloud computing, internet of things, etc.). Second, the necessity to explore new strategic, organizational and human dimensions of digital supply chain is underlined. Third, the papers included in this special issue addressing digital supply chain issues are shortly pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(128 citation statements)
references
References 21 publications
(13 reference statements)
0
67
0
4
Order By: Relevance
“…Further, these studies offer no influential or consistent termination point in their conclusions. Ageron et al (2020) and Panahifar et al (2018) found only a common theoretical foundation of digital supply chain, but this study lacks conceptual models that can be used as practical projects for digitalizing supply chain and firm performance. There is a need for quantitative empirical analysis and a conceptual framework using the most recent data and techniques such as Smart PLS (Hair et al, 2020).…”
Section: Introductionmentioning
confidence: 88%
“…Further, these studies offer no influential or consistent termination point in their conclusions. Ageron et al (2020) and Panahifar et al (2018) found only a common theoretical foundation of digital supply chain, but this study lacks conceptual models that can be used as practical projects for digitalizing supply chain and firm performance. There is a need for quantitative empirical analysis and a conceptual framework using the most recent data and techniques such as Smart PLS (Hair et al, 2020).…”
Section: Introductionmentioning
confidence: 88%
“…Thirdly, there is no doubt operational performance is an important and necessary component of several performance measurement systems currently in use [35,38], albeit the findings are not always consistent. Lastly, Neely [39], Ageron, et al [40], stated that operational performance can be dependent upon quality, costs, productivity, flexibility, and dependability. In addition, based on previous studies carried out by Maani and Sluti [41], Ward and Duray [42], Wong et al [43], and Tracey et al [44], quality, productivity, and cost have been chosen as the performance factors.…”
Section: Operational Performancementioning
confidence: 99%
“…Few studies have linked the level of supply chain integration with a firm's performance and have found a positive relationship between them [Power, 2005]. Recent studies have explored the impact of the technological intervention on supply chain integration [Büyüközkan, Göçer, 2018;Kamble et al, 2020;Ageron et al, 2020].…”
Section: Integrationmentioning
confidence: 99%